BEYOND GROWTH: HOW MORAL FAILURE AND TOXIC CULTURE TRIGGERED EFISHERY'S FRAUD - Ghina Saumalia; Yusnaini, Yusnaini (Cahaya Ilmu Bangsa, 2025)
Fraud in the startup ecosystem has become a growing concern, especially with the recent case of eFishery, which allegedly manipulated financial reports in a systematic manner. This study aims to examine the key factors contributing to fraud in startups by focusing on two critical aspects: weak individual morality and unethical organizational culture. The research employs a systematic literature review of 17 scientific articles indexed in Scopus and SINTA. The analysis reveals that both factors are interrelated and jointly foster conditions that enable fraudulent behavior. Low individual morality increases the likelihood of deviant financial decision-making, while a permissive organizational culture exacerbates the risk of fraud. The study highlights the importance of fostering ethical values and strengthening internal control systems to prevent fraud in startups, particularly those operating under high growth pressure. These findings are expected to serve as a reference for developing more accountable and integrity-driven governance in the startup environment.